2019
DOI: 10.1097/aog.0000000000003156
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Stepwise Approach to Reducing In-Hospital Opioid Use After Cesarean Delivery

Abstract: OBJECTIVE: To evaluate the association of a standardized, structured approach to in-hospital postcesarean delivery pain management with maternal opioid use after cesarean delivery. METHODS: We conducted a retrospective cohort study of women who underwent cesarean delivery before and after a quality improvement intervention at a single tertiary care center. A multidisciplinary task force revised electronic order sets for all patients who underwent cesare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 12 publications
7
60
1
6
Order By: Relevance
“…16,26 Opioid-sparing pain protocols for cesarean delivery have been shown to successfully decrease opioid prescribing while maintaining patient comfort. 27,28 These protocols include 3 main components: patient preparation (when cesarean delivery is scheduled), perioperative measures, and multimodal postoperative therapy. Preparation can help patients set expectations and develop coping techniques prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,26 Opioid-sparing pain protocols for cesarean delivery have been shown to successfully decrease opioid prescribing while maintaining patient comfort. 27,28 These protocols include 3 main components: patient preparation (when cesarean delivery is scheduled), perioperative measures, and multimodal postoperative therapy. Preparation can help patients set expectations and develop coping techniques prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Similarly, using scheduled nonnarcotic medications, such as acetaminophen and ketorolac or ibuprofen, has been shown to reduce the total OME requirement per patient. 27,28 Enhanced Recovery After Surgery protocols for obstetrics have the potential to coordinate pain management across the delivery episode through standardized protocols. 30,31,32 However, there is a lack of data on appropriate pain management techniques following vaginal delivery, and more work is needed to understand the role of opioids and opioid-sparing pain protocols for both vaginal delivery and cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
“…One highquality retrospective cohort study saw a substantial reduction in opioids as COX-2 inhibitors and NSAIDs were administered (Cozowics et al, 2019). Contrastingly, another good quality retrospective cohort study found that as acetaminophen use per day increased in combination with NSAID administration, the primary outcome of median morphine milligram equivalents administered reduced (Smith et al, 2019).…”
Section: Multimodal Analgesiamentioning
confidence: 89%
“…Several studies support the use of non-opioid analgesics (acetaminophen, NSAIDs, COX-2 inhibitors, and gabapentin/pregabalin) both preoperatively and postoperatively to improve pain management (Cozowics et al, 2019, Smith, Young, Blosser, & Poole, 2019Desai et al, 2018;Militsakh et al, 2018;Brandal et al, 2017;Brubaker, Kendall, & Reina, 2016). One highquality retrospective cohort study saw a substantial reduction in opioids as COX-2 inhibitors and NSAIDs were administered (Cozowics et al, 2019).…”
Section: Multimodal Analgesiamentioning
confidence: 99%
See 1 more Smart Citation